Cytotoxic and α-glucosidase inhibitory metabolites from twigs and leaves of Phyllanthus mirabilis, a species endemic to limestone mountains. (February 2022) - Somteds, Apisara; Kanokmedhakul, Kwanjai; Chaiyosang, Boonyanoot; Yahuafai, Jantana; Laphookhieo, Surat; Phukhatmuen, Piyaporn; Pornpongrungrueng, Pimwadee; Kanokmedhakul, Somdej
Abstract: The first investigation of Phyllanthus mirabilis Müll.Arg. led to the isolation of six undescribed compounds including two tyramine derivatives: phyllatyramines A and B; three butenolide analogues, phyllantenolide, phyllantenocoside- O -gallate and epi -phyllantenocoside- O -gallate; and a flavanonol gallate, (−)-taxifolin-3- O -gallate; as well as two first isolated natural products, phyllatyramine C and phyllantenocoside; together with twenty-three known compounds. Their structures were elucidated by spectroscopic means. ECD spectra of all isolated butenolides were compared and assigned the configurations. Phyllatyramine A displayed weak cytotoxicity against the KB cell line, while phyllatyramines B and C showed weak cytotoxicity against KB and HeLa cell lines. In addition, phyllatyramine B and (−)-taxifolin-3- O -gallate showed more potent α-glucosidase inhibitory activity than the standard acarbose 3.4 and 5.8 fold, respectively. Graphical abstract: Image 1 Highlights: Metabolites and bioactivity from limestone mountains plant, Phyllanthus mirabillis . 6 Undescribed: 2 tyramines, 3 butenolides and a flavanone were isolated. ECD spectra of all isolated butenolides were compared. Phyllatyramine B showed α -glucosidase inhibition of 3.4 fold more than acarbose. Taxifolin- O -gallate showed α -glucosidase inhibition of 5.8 fold more than acarbose.